Clinical and microbiological characteristics of bloodstream infections in hematological cancer patients - V. N. Chebotkevich; S. S. Bessmel’tsev; E. E. Kiseleva; N. P. Stizhak; E. I. Kaytandzhan; V. V. Burylev (Онкогематология)
Introduction. Bloodstream infections (BSI) are life-threatening illness for immunocompromised patients with hematological malignancies.The aim of the study was to compare epidemiology, causative pathogens and outcome of hospital-acquired BSI and clarifying the role of herpes group of viruses in their development.Materials and methods. During the period 1991–2013 438 bacterial strains obtained from 360 patients (pts) with hematological malignancies wеre studied. All blood cultures were incubated in the continuous monitoring system for 7 days before discard. The real-time PCR was used for human herpesviruses DNA detection: Herpes simplex viruses types 1 and 2 (HSV 1, 2), Cytomegalovirus (CMV), Epstein–Barr virus(EBV) and Herpesvirus 6 (HHV-6). In this study 64 hematological cancer patients with infectious complications who fulfilled criteria of systemic inflammatory response syndrome with positive peripheral blood cultures were investigated. All pts received empirical anti-infectious therapy with subsequent correction based on the bacteriological, virological and mycological analyses.Results and discussion. A total Gram-positive (G+) accounted for 69.2 % of BSI, Gram-negative (G–) for 30.8 %. Among G+ BSI Coagulase Negative Staphylococci and Staphylococcus aureus were the most frequent pathogens (58.8 %), among G– BSI Escherichia coli (13.0 %) was predominant. It is shown that the development of bacteremia were significantly more frequently occurs in the case of cytomegalovirusand the Epstein–Barr virus detection.Conclusion. Further epidemiological surveillance is warranted in order emerging resistant strains and related mortality. Reactivation of CMV and EBV is significantly associated with higher incidence of bacterial BSI.